IMPROVING STUDENTS’ WRITING RECOUNT ACHIEVEMENT THROUGH PEER REVIEW TECHNIQUE - Nina Surya Rahman Nasution; Masitowarni Siregar (TRANSFORM : Journal of English Language Teaching and Learning, 2013)
ABSTRACT Writing, regarded as a thinking process enables language learners to explore and transform their ideas into words in accurate and appropriate ways. Although it has been taught from the Elementary school level up to the higher level of education, English teachers and students encounter various challenges. For students, they still get difficulties in writing a text even after being taught. For teachers, correcting students’ writing increases their workload. Therefore, how to reduce the load of teaching writing and to decrease students’ difficulties in writing have become important problem to solve. Through applying a technique in teaching writing, this research aimed to explore whether the application of peer review technique can improve students’ achievement in writing recount text. The method applied in this research was a classroom action research. The subject of the research was X-4 class SMA Negeri 21 Medan. The instruments of collecting the data were writing tasks as quantitative data while observation sheet, questionnaire sheet, diary notes and interview as qualitative data. The finding showed that Peer Review Technique gives contribution to improve students’ achievement in writing recount text. Keywords: Achievement, Writing, Recount Text, Peer Review Technique